Tournament tips
Multi-event or multi-training days require a special nutrition. Why? •To replace fluid levels, preventing excessive dehydration; •To prevent excessive changes in electrolyte balance; •To provide energy before and during training or competition; •To prevent hunger; •To supply food that is quickly and easily digested; •To ensure energy and nutrients to recover and prepare for the next training session or competitive event.